A novel peptide inhibitor of TRPM2 channels improves recovery of memory function following traumatic brain injury - James E. Orfila; Robert M. Dietz; Christian Schroeder; Olivia P. Patsos; Amelia Burch; Kiara E. Bahamonde; Kelley A. Coakley; Danelle J. Carter; Amy C. Clevenger; Tara B. Hendry-Hofer; Tuan D. Le; Joseph K. Maddry; et al. (Frontiers in Synaptic Neuroscience)
Traumatic Brain Injury (TBI) is a leading cause of mortality and morbidity in adults and can lead to long-term disability, including cognitive and motor deficits. Despite advances in research, there are currently no pharmacological interventions to improve outcomes after TBI. Studies suggest that non-selective transient receptor potential melastatin 2 (TRPM2) channels contribute to brain injury in models of ischemia, however TRPM2 remains understudied following TBI. Thus, we utilized TRPM2 KO mice and a novel TRPM2 inhibiting peptide, tatM2NX, to assess the role of TRPM2 in TBI-induced injury and functional recovery. This study used histological analysis of injury, neurobehavior and electrophysiology to assess the role of TRPM2 on injury and cognitive recovery (memory) impairments using the controlled cortical impact (CCI) model to induce TBI in mice. Histological analysis used to investigate brain injury volume at 7 days after TBI showed sex differences in response to injury in TRPM2 KO mice but no pharmacological effects in our WT mice. A contextual fear-conditioning task was used to study memory function 7 or 30 days after TBI and demonstrates that sham-operated mice exhibited significant freezing behavior compared to TBI-operated mice, indicating impaired memory function. Mice administered tat-M2NX 2 h after TBI exhibited a significant reduction of freezing behavior compared to control tat-scrambled (tat-SCR)-treated mice, suggesting improvement in memory function after TBI. To test the effect of TBI on hippocampal long-term potentiation (LTP), a well-established cellular model of synaptic plasticity associated with changes in learning and memory, extracellular field recordings of CA1 neurons were performed in hippocampal slices prepared 7 days after TBI. Consistent with our behavioral testing, we observed impaired hippocampal LTP in mice following TBI (tat-SCR), compared to sham control mice. However, mice treated with tat-M2NX after TBI exhibited preserved LTP, consistent with the improved memory function observed in our behavioral studies. While this data implicates TRPM2 in brain pathology following TBI, the improvement in memory function without providing histological protection suggests that administration of tatM2NX at an acute time point differentially affects hippocampal regions compared to cortical regions.